ANALISIS STRATEGI PENINGKATAN PEMBIAYAAN MULTI GUNA (PMG) PADA PT. BANK SUMUT UNIT USAHA SYARIAH - Atika, Atika; Putri, Riri Dwita (Universitas Dharmawangsa, 2024)
Multipurpose Financing is the financing of goods and/or services required by the debtor for use/consumption and not for business purposes or productive activities within the agreed period. The role of multi-use payments in banks is to provide flexible and versatile payment services for customers, allowing them to conduct various types of financial transactions through a single platform or payment method. Based on this background, the research objective is to analyze the multi-use payment strategy (PMT) at PT Bank Sumut Syariah Unit Medan. This research uses a qualitative method with a descriptive approach. Research on increasing Multi-Use Financing (PMG) at PT Bank Sumut Syariah Business Unit aims to analyze bank strategies using qualitative methods and SWOT analysis. The results show great opportunities for banks, such as increasing public demand, low penetration of Islamic financing, and government support. However, the challenges faced include fierce competition, lack of public education, and complicated financing processes. Based on SWOT analysis, strategies that can be applied include increasing education, utilizing information technology, and offering products that suit the needs of the community, in order to make PT Bank Sumut Syariah Business Unit the leading Islamic bank in Indonesia.